The Empower Nudge lottery to increase dual protection use: a proof-of-concept randomised pilot trial in South Africa. Issue 52 (1st January 2018) - Galárraga, Omar; Harries, Jane; Maughan-Brown, Brendan; Cooper, Diane; Short, Susan E; Lurie, Mark N; Harrison, Abigail
Abstract: The objective of this study is to measure the preliminary efficacy of a pilot intervention, grounded in behavioural economics, increasing adherence of dual protection (simultaneous use of effective modern contraception and a barrier method, such as a condom) to protect against HIV, other sexually transmitted infections, and unintended pregnancy. Between 2015 and 2016, 100 women aged 18–40 years, seeking post-abortion care in Cape Town, South Africa were recruited to Empower Nudge, a randomised controlled trial to test a lottery incentive intervention designed to increase dual protection. At baseline, the mean age of participants was 27 years; 82% of them were from South Africa; 58% self-identified as Black African; average education completed was 11.7 years. At three months, assignment to the lottery intervention was associated with higher odds of returning for study visits (OR: 6.0; 95%CI: 2.45 to 14.7, p < 0.01), higher condom use (OR: 4.5; 95%CI: 1.43 to 14.1; p < 0.05), and higher use of dual protection (OR: 3.16; 95%CI: 1.01 to 9.9; p < 0.05). Only 60% of the study population returned after three months and only 38% returned after six months. Women who receive post-abortion care represent a neglected population with an urgent need for HIV and pregnancy prevention. Dual protection is a critically important strategy for this population. Lottery-based behavioural economics strategies may offer possible ways to increase dual protection use in this population. Further research with larger samples, longer exposure time, and more sites is needed to establish fully powered efficacy of lottery incentives for dual protection; using objective verification for monitoring.